ENGLISH LEARNERS’ STRATEGIES OF LEARNING READING COMPREHENSION ACROSS DIFFERENT GENDERS - Agista Fara Amalia Hermawanti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article presents English learners’ strategies of learning reading comprehension across genders. The aims of this study was to know the intensity of the reading strategy used by second semester students of University of Islam Malang and to know the reading strategies used the most by male and female students of University of Islam Malang. This research employed quantitative approach. The sample of this study was 40 students of English education department that consist of 20 male students and 20 female students. The finding showed the intensity strategy that used by students from three categories were N = 33 students with average high score (GLOB: M = 4.22; PROB: M = 4.53; SUP: M = 4.19). Meanwhile, the strategies that frequently used by the male students were (GLOB: M = 4.35; PROB: M = 4.45: SUP: M = 4.20) and female students (GLOB: M = 4.97; PROB: M = 4.56; SUP: M = 4.21) with total students most used strategy were male 18 and female 15. Male students frequently employed the approach of double-checking their knowledge whenever they encountered new information, read broad information fast in the text and ask dense questions to find answers in the book while, female students used the text's keyword to comprehend what they read, read the material twice to determine the relationship between the information and only read the opening and conclusion before reading the entire text. Based on the research findings, the researcher concluded that most of the students were classified as high strategy usage of Global Reading Strategy, Problem Solving Strategy and Support Reading Strategy. Meanwhile, male and female students had some similarities and diffirences in utilizing those three catagories in comprehending the text. Key Words: Reading strategy, Gender students